1999
DOI: 10.1016/s0885-3924(99)00054-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Postradical Neck Pain Syndrome

Abstract: The postradical neck pain syndrome has been briefly described in the literature, but detailed characterization has not been reported. To further define this syndrome, 25 patients with persistent pain for at least 1 month following neck dissection were evaluated. The sample consisted of 13 men and 12 women with moderate to severe pain ranging from 1 month to 27 years in duration. All patients had at least one type of neuropathic pain: spontaneous, continuous burning pain (81%), shooting pain (69%), and/or allod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
1
17
0
10
Order By: Relevance
“…The chance for microtraumata may be more likely because of the anatomical variations in the course of the nerve, particularly in the passage of the sternocleidomastoid muscle, which may lead to more extensive damage [27,21]. But with an intact spinal accessory nerve and trapezius muscle function still shoulder complaints may arise which are interpreted as neuropathic pain or myofascial pain [28].…”
Section: Discussionmentioning
confidence: 99%
“…The chance for microtraumata may be more likely because of the anatomical variations in the course of the nerve, particularly in the passage of the sternocleidomastoid muscle, which may lead to more extensive damage [27,21]. But with an intact spinal accessory nerve and trapezius muscle function still shoulder complaints may arise which are interpreted as neuropathic pain or myofascial pain [28].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain for patients with head and neck cancer may involve all sensory nerves in the face, skull, neck and shoulders (Vecht et al, 1992). Some common symptoms of neuropathic pain experienced by the patients include spontaneous continuous burning (81%), shooting pain (69%) and allodynia (88%) -which describes abnormal pain elicited by light touch (Sist et al, 1999;Merskey & Bogduk, 1994). The percentage of patients with head and neck cancer in various studies who were assessed to have neuropathic pain is shown in …”
Section: Aetiology Of Painmentioning
confidence: 99%
“…Bei Patienten mit gesichertem PRNS liegt häufig eine signifikante Beeinträchtigung der Lebensqualität durch das insbesondere neuropathische Schmerzsyndrom vor, was die Notwendigkeit zur Evaluierung effektiver Therapieformen unterstreicht [10].…”
Section: Fallbeschreibungunclassified
“…Nach totaler Thyroidektomie beidseits mit modifiziert radikaler Neck-Dissection links mit Entfernung der Glandula submandibularis, gefolgt von einer NeckDissection rechts 2 Wochen später mit anschließender ablativer Radiojodtherapie mit 8180 MBq(131)I per os entwickelte die Patientin ein zunehmendes Schmerzsyndrom mit einer Allodynie der Dermatome C3-5 links gepaart mit einer Hyperästhesie vom linken Ohr bis in den Kieferwinkel ziehend mit leicht ödematöser Schwellung insbesondere der gesamten Scalenus-posterior-Muskulatur links mit multiplen druckdolenten Triggerpunkten, welche sich retroskalenisch über den Nacken und die linke Trapeziusregion verteilten, womit sie die Kriterien eines PRNS erfüllte [10].…”
Section: Diskussionunclassified